Ramucirumab versus placebo in combination with second-line FOLFIRI in patients with metastatic colorectal carcinoma that progressed during or after first-line therapy with bevacizumab, oxaliplatin, and a fluoropyrimidine (RAISE): a randomised, double-blind, multicentre, phase 3 study. Issue 5 (May 2015) - Tabernero, Josep; Yoshino, Takayuki; Cohn, Allen Lee; Obermannova, Radka; Bodoky, Gyorgy; Garcia-Carbonero, Rocio; Ciuleanu, Tudor-Eliade; Portnoy, David C; Van Cutsem, Eric; Grothey, Axel; Prausová, Jana; Garcia-Alfonso, Pilar; et al.
Summary: Background: Angiogenesis is an important therapeutic target in colorectal carcinoma. Ramucirumab is a human IgG-1 monoclonal antibody that targets the extracellular domain of VEGF receptor 2. We assessed the efficacy and safety of ramucirumab versus placebo in combination with second-line FOLFIRI (leucovorin, fluorouracil, and irinotecan) for metastatic colorectal cancer in patients with disease progression during or after first-line therapy with bevacizumab, oxaliplatin, and a fluoropyrimidine. Methods: Between Dec 14, 2010, and Aug 23, 2013, we enrolled patients into the multicentre, randomised, double-blind, phase 3 RAISE trial. Eligible patients had disease progression during or within 6 months of the last dose of first-line therapy. Patients were randomised (1:1) via a centralised, interactive voice-response system to receive 8 mg/kg intravenous ramucirumab plus FOLFIRI or matching placebo plus FOLFIRI every 2 weeks until disease progression, unacceptable toxic effects, or death. Randomisation was stratified by region, KRAS mutation status, and time to disease progression after starting first-line treatment. The primary endpoint was overall survival in the intention-to-treat population. This study is registered withClinicalTrials.gov, numberNCT01183780 .ld Findings: We enrolled 1072 patients (536 in each group). Median overall survival was 13·3 months (95% CI 12·4–14·5) for patients in the ramucirumab group versus 11·7 months (10·8–12·7) for the placebo group (hazard ratio 0·844 95% CI 0·730–0·976; log-rank p=0·0219). Survival benefit was consistent across subgroups of patients who received ramucirumab plus FOLFIRI. Grade 3 or worse adverse events seen in more than 5% of patients were neutropenia (203 [38%] of 529 patients in the ramucirumab group vs 123 [23%] of 528 in the placebo group, with febrile neutropenia incidence of 18 [3%] vs 13 [2%]), hypertension (59 [11%] vs 15 [3%]), diarrhoea (57 [11%] vs 51 [10%]), and fatigue (61 [12%] vs 41 [8%]). Interpretation: Ramucirumab plus FOLFIRI significantly improved overall survival compared with placebo plus FOLFIRI as second-line treatment for patients with metastatic colorectal carcinoma. No unexpected adverse events were identified and toxic effects were manageable. Funding: Eli Lilly.